(untitled) (Global Journal of Management and Business Research, 2024)
In Bangladesh family businesses play a significant role in the country s business landscape because so few private companies are set up as large-scale non-family ownership firms Thus it is vital to comprehend family businesses in order to comprehend Bangladeshi company dynamics In this paper authors attempted to survey the existing research in the area of family business in Bangladesh It was found that the area as a research is totally an open field and a lot of new research can be done in the said area Although a good number of studies can be classified as focused on the SME small and medium enterprise domain a major shortcoming of those SME studies is that the SMEs themselves vary greatly in terms of size scope and technology Whereas most of the family businesses predominantly can be put in the SME category the particular issue of family business and family dynamics is not very common in those studies This paper suggests that a good amount of research or studies can be done focusing on family business constitution family member s participation norm recruitment and promotion norm family business succession rules and succession planning training for family business leadership and management training for board and directorial supervision and so on